Synthesis of polysulfide adsorbent from waste cooking palm oil for the removal of iron (ⅲ) - Abdullah, Nayeem (2022)
Elemental sulfur and waste cooking palm oil (WCO) are abundant industrial by-products from the petrochemical and food processing industries, respectively. WCO has been successfully used as a crosslinker to prepare a high-sulfur-content polymer through inverse vulcanization for the removal of ferric ions (Fe3+) in wastewater. In the current work, WCO has been characterized using GC-MS, FTIR, and TGA to assess the feasibility to be used as a crosslinker in inverse vulcanization. The produced polysulfides were analyzed based on the different reaction parameters including sulfur to WCO crosslinking ratio, temperature, time, and the application of NaCl by FTIR, TGA, XRD, SEM-EDX, and BET. The adsorption process was studied by varying pH, initial Fe3+ concentration, and dosage with suitable isothermal and kinetic studies. The required functional bonds and unsaturation of WCO were confirmed by FTIR and GC-MS, and the stability at higher temperatures was confirmed using TGA. Polysulfides were synthesized under stirring (500 rpm) of WCO with elemental sulfur at three different temperatures (195℃, 190℃, and 185℃) with three crosslinking ratios (70, 60, and 50 wt% sulfur). Two different sets of reaction time; 45 min and 60 min have been used for polysulfide synthesis. The physicochemical properties of the produced polysulfides were determined and the thermal stability was analyzed. The FTIR spectra including the breakdown of C=C and formation of C–S bond confirmed the change of functional groups between WCO and produced polymer. The effect of saturated and unsaturated triglycerides of WCO is clearly visible in SEM micrographs. The polysulfide with a 70 wt % sulfur feed ratio showed better surface area . TGA and DTG showed that better thermal properties and stable polysulfides can be obtained from higher amount of sulfur content. Other optimal conditions for inverse vulcanization were recorded as well, such as 60 min of reaction time and 195℃. The surface was modified using NaCl as porogen to increase surface area. The BET results confirmed the increase of the surface area of the porous polysulfides prepared using NaCl. Removal performance was evaluated by studying the effects of parameters including porosity, pH of the solution, initial Fe3+ concentration, and amount of polysulfide dosages. The highest removal was recorded for porous polysulfides. Acidic pH (pH=3) was favorable for Fe3+ removal. The optimum dosage was 20 mg/100 mL. The removal isotherm has been studied and fitted best for Freundlich isotherm. The kinetic study of the removal process has been fit well in linear pseudo second order kinetic model. It is concluded that inverse vulcanized polysulfides can be successfully used to reduce Fe3+ in wastewater and mitigate the environmental threats of excess WCO.